IMPLEMENTASI PROGRAM SUSTAINABLE DEVELOPMENT GOALS INDONESIA ONE-GREEN FINANCE FACILITY (SIO-GFF) OLEH PT SARANA MULTI INFRASTRUKTUR (PERSERO) PERIODE 2022 - 2024 - Santoso, Sagit Hartono; Audria, Natasya (Moestopo Journal of International Relations (MJIR), 2024)
This research aims to analyze the implementation of the Sustainable Development Goals Indonesia One-Green Finance Facility (SIO-GFF) program as a form of effort to improve the Indonesian economy after COVID-19. The research method used is a descriptive research method with a qualitative approach, where data collection is carried out through book sources, journal articles, theses and also internet sites. This research uses Interdependence theory to explain how the SIO-GFF program is implemented and to explain the success of the program. The research results show that the SIO-GFF program can attract the attention of the public, both local and international financial institutions and the private sector.